Attention-deficit/hyperactivity disorder in a population isolate : linkage to Loci at 4q13.2, 5q33.3, 11q22, and 17p11 (2004)
ABSTRACT: Attention-deficit/hyperactivity disorder (ADHD [MIM 143465]) is the most common behavioral disorder of childhood. Twin, adoption, segregation, association, and linkage studies have confirmed that genetics plays a major role in conferring susceptibility to ADHD. We applied model-based and model-free linkage analyses, as well as the pedigree disequilibrium test, to the results of a genome wide scan of extended and multigenerational families with ADHD from a genetic isolate. In these families, ADHD is highly comorbid with conduct and oppositional defiant disorders, as well as with alcohol and tobacco dependence. We found evidence of linkage to markers at chromosomes 4q13.2, 5q33.3, 8q11.23, 11q22, and 17p11 in individual families. Fine mapping applied to these regions resulted in significant linkage in the combined families at chromosomes 4q13.2 (two-point allele-sharing LOD score from LODPAL p 4.44 at D4S3248), 5q33.3 (two-point allele-sharing LOD score from LODPAL p 8.22 at D5S490), 11q22 (two-point allele-sharing LOD score from LODPAL p 5.77 at D11S1998; multipoint nonparametric linkage [NPL] 5log [P value] p 5.49 at ∼128 cM), and 17p11 (multipoint NPL 5log [P value] 112 at ∼12 cM; multipoint maximum location score 2.48 [a p 0.10] at ∼12 cM; two-point allele-sharing LOD score from LODPAL p 3.73 at D17S1159). Additionally, suggestive linkage was found at chromosome 8q11.23 (combined two-point NPL5log [P value] 13.0 at D8S2332). Several of these regions are novel (4q13.2, 5q33.3, and 8q11.23), whereas others replicate already-published loci (11q22 and 17p11). The concordance between results from different analytical methods of linkage and the replication of data between two independent studies suggest that these loci truly harbor ADHD susceptibility genes.